Understanding Typhoid in the American Civil War: A Study of Typhoid Within the Union and Confederate Armies, 1861-1865 - Robinson, Nick (My University, 2017)
In this paper, I want the reader to understand and become familiar with the topic of typhoid fever in the American Civil War from 1861 to 1865. It was during the 19th century that typhoid fever emerged as a deadly infectious disease in which there were no effective treatments. Early in the war, from 1861-1863, this infectious disease spread from camp to camp, causing men to become sick and die. This period early in the war was called the medical middle ages due to a lack of knowledge towards infectious diseases and what made them so lethal. Typhoid fever was one of several infectious diseases that emerged in 1861 during the first year of the war. At the start of the war, in both the Confederate and Union armies, there were few doctors to help against this disease. Many of these doctors were inexperienced in the way of medicine, and therefore, were unable to stop the spread of these diseases that caused more deaths than battlefield wounds. For this paper, I want to analyze and explain what made typhoid fever such a deadly disease from 1861 to 1863 when the practice of medicine was in its infancy. My goal in this paper is to separate typhoid into two periods. The first period, from 1861 to 1863, I will go into detail on the severity of typhoid fever. In 1861, neither side was prepared for such a long war, and therefore, were ill prepared to treat diseases like typhoid fever that caused thousands of deaths. For the second period, from 1864 to 1865, I will look at the efforts and solutions put forth by both sides to decrease the severity of this infectious disease.
Series: USGZE AS333
Keywords: United States--History--Civil War, 1861-1865--Health aspects.; Typhoid fever--United States.; Communicable diseases--United States--History--19th century.